2011
DOI: 10.3109/13625187.2011.608441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a women's counselling programme on combined hormonal contraception in Portugal – The IMAGINE Study

Abstract: The implementation of a counselling programme significantly affected contraceptive choices leading in a number of cases to the selection of alternatives better suited to women's lifestyle. Age and educational level are socio-demographic factors which play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
6
0
5
Order By: Relevance
“…The overall results of CHOICE confirmed the findings of TEAM-069 and IMAGINE,13 and indicated that counseling encouraged women to learn about and choose alternative forms of contraception that may be different from the method intended before consulting with their health care practitioner, including the pill, patch, and ring, as well as other methods. However, considerable differences were noted among the various countries included in CHOICE.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The overall results of CHOICE confirmed the findings of TEAM-069 and IMAGINE,13 and indicated that counseling encouraged women to learn about and choose alternative forms of contraception that may be different from the method intended before consulting with their health care practitioner, including the pill, patch, and ring, as well as other methods. However, considerable differences were noted among the various countries included in CHOICE.…”
Section: Introductionsupporting
confidence: 60%
“…After counseling, the women were surveyed to ascertain the reasons for their choices. A similar study, IMAGINE (IMpacto de um programa de informAção pelos GINEcologistas na contracepção hormonal combinada, em Portugal), was performed in Portugal 13. In both studies, the pill was the most preferred method before counseling; however, after counseling, a significantly higher number of women chose other methods, eg, the patch or ring, indicating that the selected method better fit their life circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies, performed in different European countries, have confirmed the preliminary data from the TEAM study, shown that the information facilitated may help women make decisions, and corroborated that the vaginal ring is a highly regarded option among users. [62][63][64][65][66][67][68] One of the parameters that measures acceptability of a contraceptive method is the continuation rate. A prospective study, with follow-up lasting 12 cycles, enrolled 3,443 women who started using a COC, patch, or ring.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Previous research has shown that providing women with information about CHC not only improves their knowledge and awareness of risks but also allows them to make a more informed choice [8-10]. Studies have also reported that receiving information about contraception has encouraged women to opt for alternative methods than those they had initially considered [9,10].…”
Section: Introductionmentioning
confidence: 99%